A sulfur and nitrogen-rich heteroaromatic ring organic molecule composite electrode material, a preparation method therefor, and an application thereof
Patent Information
- Application Number
- CN202611304188.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-23
AI Technical Summary
[0007]针对现有MXene电极片层严重堆叠、传统改性材料界面相容性差、氧化还原有机小分子活性位点不足、超级电容器工作电压窄、能量密度低、循环容量衰减快等技术问题,本发明提供了一种富硫氮杂芳环有机分子复合电极材料,同时提供了该材料的制备方法和应用
[0026](1)多杂原子共轭分子,提供丰富赝电容活性位点
Smart Images

Figure CN122968133A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage electrode material technology, specifically relating to a sulfur- and nitrogen-rich heteroaromatic ring organic molecule composite electrode material, its preparation method, and its application. Background Technology
[0002] Two-dimensional transition metal carbides Ti3C2T x MXene, with its metallic conductivity, abundant hydrophilic functional groups, tunable interlayer spacing, and intrinsic intercalation pseudocapacitance, is one of the electrode substrates for supercapacitors. However, Ti3C2T... x The presence of van der Waals forces and hydrogen bonds between MXene nanosheets makes them prone to stacking and agglomeration, which compresses the effective specific surface area of the material and blocks the ion transport channels of the electrolyte, resulting in a significant decrease in electrode specific capacitance and energy density, thus limiting its actual energy storage performance.
[0003] Existing modification schemes for improving MXene sheet stacking mainly fall into three categories: carbon-based material composites, metal oxide composites, and conductive polymer composites. Carbon materials such as carbon nanotubes and graphene have weak interfacial bonding with MXene, making them prone to phase separation during cycling. Metal oxides have poor conductivity, are prone to pulverization, and have insufficient long-term cycling stability. Conductive polymers such as polyaniline and polypyrrole have cumbersome preparation processes, and their stable voltage window is narrow in aqueous systems, limiting the improvement in energy density.
[0004] Redox-active small organic molecules have become candidate materials for MXene modification due to their advantages such as designable molecular structure, controllable redox sites, and simple synthesis processes. Currently reported phenazine and phenothiazine small organic molecules contain only a small number of N / S heteroatoms, have a limited number of redox-active sites, and have poor intrinsic conductivity, are prone to dissolution and loss in electrolytes, and are prone to aggregation. They cannot simultaneously solve multiple problems such as MXene stacking, poor conductivity of organic molecules, low energy density of devices, and rapid cycle decay.
[0005] The existing technology has not yet disclosed the use of benzothiazole, fluoren[2,3-b:3',2'-d]dithiophene dual heterocyclic units, and conjugated organic molecules (CBT) rich in sulfur and nitrogen dual heteroatoms for MXene intercalation modification; there is a lack of composite electrode preparation schemes that can expand the MXene interlayer through π-π interactions, construct strong S / N-Ti interface electronic coupling, and simultaneously exert the synergistic effect of MXene double-layer capacitance and organic molecule multi-electron pseudocapacitance; at the same time, existing MXene-based aqueous supercapacitors generally have problems such as voltage windows below 1.0V, difficulty in breaking through energy density, and low capacity retention during long cycles.
[0006] Purpose of the invention
[0007] To address the technical problems of existing MXene electrode layers, such as severe stacking, poor interfacial compatibility of traditional modified materials, insufficient active sites of redox organic small molecules, narrow operating voltage of supercapacitors, low energy density, and rapid capacity decay during cycling, this invention provides a sulfur- and nitrogen-rich heteroaromatic ring organic molecule composite electrode material, along with its preparation method and applications. To achieve the above objectives, the technical solution adopted by this invention is as follows:
[0008] In a first aspect, the present invention provides a sulfur- and nitrogen-rich heterocyclic aromatic ring organic molecule composite electrode material, wherein the composite electrode material comprises Ti3C2T x MXene and sulfur- and nitrogen-rich heterocyclic aromatic organic molecule CBT; said CBT has the following structural formula:
[0009]
[0010] The CBT is a conjugated heterocyclic aromatic molecule prepared by the Suzuki-Miyaura coupling reaction. The molecular skeleton contains both fluorenzo[2,3-b:3',2'-d]dithiophene and benzothiazole units. The molecule is rich in S and N dual heteroatoms and has multiple reversible redox sites. The CBT molecule is embedded in the MXene interlayer, and the molecular conjugated π system generates π-π interactions with MXene. The S and N heteroatoms of CBT form an electronic coupling interface with the Ti sites on the MXene surface.
[0011] Furthermore, the CBT has the following NMR characterization data: 1 H NMR (400 MHz, CDCl3): 8.04 (d,J = 3.6 Hz, 2H), 7.90 (d, J = 8.8 Hz, 2H), 7.83 (d, J = 6.8 Hz, 2H), 7.64\7.60 (m, 2H), 7.26\7.23 (m, 2H), 1.55 (s, 6H);
[0012] 13 CNMR (101 MHz, CDCl3): 161.4, 155.6, 152.1, 139.8, 137.9, 137.4, 134.9, 129.7, 128.6, 127.3, 124.7, 123.5, 119.9, 118.0, 45.7, 25.1.
[0013] Secondly, the present invention provides a method for preparing the sulfur-rich nitrogen-rich heteroaromatic ring organic molecule composite electrode material, comprising the following steps:
[0014] (1) Ti3C2T xMXene powder was dispersed in deionized water to prepare an MXene suspension;
[0015] (2) Dissolve CBT in deionized water to prepare an aqueous solution of CBT;
[0016] (3) Add ascorbic acid to the MXene suspension, and add the CBT aqueous solution dropwise under stirring. Mix well to obtain a precursor mixture.
[0017] (4) The precursor mixture is transferred to a hydrothermal reactor for hydrothermal intercalation reaction;
[0018] (5) After the reaction is complete, the composite electrode material is separated, washed and dried to obtain the composite electrode material.
[0019] Furthermore, the Ti3C2T x The mass ratio of MXene to CBT is (5~20):1.
[0020] Furthermore, the Ti3C2T x The mass ratio of MXene to CBT is 10:1.
[0021] Furthermore, the hydrothermal intercalation reaction temperature is 180°C, and the reaction time is 16 hours.
[0022] Furthermore, the Ti3C2T x MXene powder was prepared by MILD etching, with the etchant being a mixed solution of LiF and hydrochloric acid, the etching temperature being 40℃, and the etching time being 48h.
[0023] Thirdly, the present invention provides the application of the composite electrode material in supercapacitors.
[0024] Fourthly, the present invention provides a symmetrical supercapacitor, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode and the negative electrode respectively comprise the composite electrode material provided by the present invention, the electrolyte is an aqueous sulfuric acid solution, and the operating voltage window of the symmetrical supercapacitor is 0~1.5V.
[0025] The beneficial effects of this invention are:
[0026] (1) Multi-heteroatom conjugated molecules provide abundant pseudocapacitive active sites.
[0027] The CBT molecule of this invention contains a conjugated framework of benzothiazole and fluorenidine dithiophene, with a large number of S and N heteroatoms providing multiple electrons for reversible redox reactions, effectively overcoming the shortcomings of pure MXene relying solely on the double layer for energy storage and the poor conductivity of pure organic small molecules. Three-electrode system 1 A g -1At the given current density, the specific capacitance of M / CBT-10 in this embodiment can reach 129.9 F g. -1 It is much higher than that of pure MXene (68.6 F g). -1 ) and pure CBT (40.6 F g) -1 ).
[0028] (2) Molecular intercalation widens the interlayer space and inhibits MXene sheet stacking. CBT, as a molecular spacer layer, is embedded between MXene sheets. The (002) diffraction peak of MXene XRD feature shifts from 8.66° to 8.54°, and the interlayer space is significantly widened; the BET specific surface area increases from 1.2 m² of pure MXene. 2 g -1 Increased to 17.6m 2 g -1 The number of micropores was significantly increased, the electrolyte ion diffusion resistance was significantly reduced, and the rate performance was improved.
[0029] (3) Strong interfacial electronic coupling, dual structural and electrochemical stability
[0030] XPS and FTIR characterizations demonstrate that the N and S atoms of CBT form stable electronic coupling with the Ti sites on the MXene surface, while the molecular conjugated π system generates π-π interactions with MXene, which not only prevents the aggregation of CBT molecules themselves but also prevents the secondary stacking of MXene nanosheets. Nyquist spectra show that the composite electrode has a steep curve in the low-frequency region, indicating excellent ion diffusion dynamics.
[0031] (4) Capacitor-dominated energy storage mechanism, suitable for high-power fast charging scenarios
[0032] Charge dynamics tests show that 100 mV / s -1 At the scan rate, the capacitor-controlled energy storage contributes 77% of the energy, and the ion adsorption and desorption reactions are fast and reversible; the capacity decay is gradual as the scan rate increases, and it has excellent high-rate charge and discharge capabilities.
[0033] (5) Symmetrical devices have significantly better performance than traditional MXene-based water storage devices.
[0034] The device obtained by this invention has a stable voltage window in water systems of up to 1.5V, which is higher than the voltage limitation range of 0.8~1.0V for traditional MXene devices;
[0035] The device obtained by this invention has a performance of 1 A / g -1 Power density 750 W / kg -1 Under these conditions, the energy density reaches as high as 23.75 Wh / kg. -1 Compared with existing MXene / polymer and MXene / metal oxide composite devices, it has significant advantages;
[0036] The device obtained by this invention retains 99.75% of its capacity and has a coulombic efficiency of 96.30% after 5000 constant current charge-discharge cycles, solving the problems of dissolution and rapid decay of organic small molecule electrolytes.
[0037] (6) The preparation process is simple and green, and is suitable for industrial promotion.
[0038] The Suzuki coupling synthesis yield of CBT molecules reaches 80%, and the raw materials are commercially available; the composite electrode only requires one step of low-temperature hydrothermal treatment, without the need for high-temperature calcination; the aqueous electrolyte is free of heavy metals and volatile toxic solvents, and the whole process is low-cost, easy to operate, and can be mass-produced. Attached Figure Description
[0039] Figure 1 This is the 1H NMR spectrum of the sulfur- and nitrogen-rich heterocyclic aromatic organic molecule CBT of this invention;
[0040] Figure 2 This is the 1H NMR spectrum of the sulfur- and nitrogen-rich heterocyclic aromatic organic molecule CBT of this invention;
[0041] Figure 3 This is a schematic diagram illustrating the application of the composite electrode material of the present invention in a symmetrical supercapacitor. Detailed Implementation
[0042] The technical solution of the present invention will be further described below with reference to the accompanying drawings and through embodiments.
[0043] In the embodiments of the present invention, the sulfur- and nitrogen-rich heterocyclic aromatic organic molecule composite electrode material provided is a novel sulfur- and nitrogen-rich heterocyclic conjugated organic molecule CBT. The molecule integrates benzothiazole and fluorenidine dithiophene heterocyclic structures. It relies on a large number of S and N heteroatoms in the molecule to construct multiple sets of reversible redox active centers, providing additional Faraday pseudocapacitance for the composite electrode.
[0044] In an embodiment of the present invention, a one-step hydrothermal method is provided for preparing CBT intercalated Ti3C2T. x The process of MXene composite electrode material utilizes CBT as a multifunctional molecular spacer layer. Through π-π interactions, it inhibits the stacking of MXene nanosheets, widens the interlayer spacing, increases the specific surface area of the material, and opens up the ion transport channels of the electrolyte.
[0045] In the embodiments of the present invention, a strong interfacial electronic coupling mechanism is constructed between CBT and MXene to enhance the overall structural stability of the composite electrode, while retaining the advantages of the high conductivity framework of MXene, thereby achieving synergistic energy storage of double-layer capacitance and multi-electron pseudocapacitance.
[0046] In an embodiment of the present invention, a symmetrical supercapacitor assembly scheme based on the composite electrode is provided, which expands the stable operating voltage window of the water-based device to 1.5V, significantly improves the energy density of the device, and achieves ultra-low capacity decay and high coulombic efficiency after 5000 long cycles.
[0047] In the embodiments of the present invention, the entire preparation process of the product uses readily available raw materials, mild reaction conditions, high synthesis yield, no high-temperature calcination process, is green and environmentally friendly, and can be mass-produced industrially.
[0048] Example 1: Ti3C2T x Preparation of MXene nanosheet precursors
[0049] (1) Weigh 1.0g of Ti3C2T x MXene powder was slowly added to the pre-prepared etching solution (1.6 g LiF dissolved in 20 mL of 9 mol / L HCl).
[0050] (2) Stir at a constant temperature of 40 °C for 48 h to completely etch and remove the Al atomic layer;
[0051] (3) Collect the precipitate by centrifugation at 5000 rpm, wash repeatedly with deionized water and centrifuge for 60 min each time until the pH of the supernatant is close to neutral.
[0052] (4) Collect the dark green upper layer dispersion (monolayer / few layers of MXene), freeze dry to obtain MXene powder, and store it in an argon glove box in a sealed, light-proof container.
[0053] Example 2: Synthesis of CBT, a sulfur- and nitrogen-rich heterocyclic organic molecule
[0054] The reaction formula is as follows:
[0055]
[0056] (1) Weighing of raw materials: Weigh 1.00 g (1.90 mmol) of 2,6-bis(5-bromothiophene-2-yl)-4,4-dimethyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene, 1.05 g (4.00 mmol) of benzothiazolium boric acid derivative, 0.22 g (0.19 mmol) of tetra(triphenylphosphine)palladium, and 0.91 g (6.65 mmol) of potassium carbonate, and add them to a dry and pressure-resistant reaction flask;
[0057] (2) Oxygen-free replacement: Seal the reaction flask, evacuate and replace with high-purity nitrogen three times to completely remove oxygen from the system;
[0058] (3) Reflux reaction: 40 mL of anhydrous tetrahydrofuran was injected under nitrogen protection and the solid was dispersed by stirring for 30 min; the oil bath was heated to 100 °C and refluxed under nitrogen atmosphere for 10 h.
[0059] (4) Extraction and separation: Cool to room temperature, add 50 mL of deionized water to dilute the reaction solution, extract with ethyl acetate 3 times, 30 mL each time; combine all organic phases and dry with anhydrous sodium sulfate to remove water;
[0060] (5) Purification and drying: The desiccant was removed by filtration, and the solvent was removed by rotary evaporation to obtain the crude product; column chromatography was performed using petroleum ether: ethyl acetate = 4:1 as the eluent, the target component was collected, and after rotary drying, it was vacuum dried to obtain 0.96 g of chestnut solid CBT, with a yield of 80%;
[0061] (6) Structural verification: Tested using a 400MHz NMR spectrometer. 1 H NMR, 13 C10 NMR confirmed that the molecular structure is consistent with the target CBT. NMR characterization data:
[0062] 1 HNMR (400 MHz, CDCl3): 8.04 (d, J = 3.6 Hz, 2H), 7.90 (d, J = 8.8 Hz,2H), 7.83 (d, J = 6.8 Hz, 2H), 7.64\7.60 (m, 2H), 7.26\7.23 (m, 2H), 1.55 (s,6H); (see attachment for details Figure 1 );
[0063] 13 CNMR (101MHz, CDCl3): 161.4, 155.6, 152.1, 139.8, 137.9, 137.4, 134.9, 129.7, 128.6, 127.3, 124.7, 123.5, 119.9, 118.0, 45.7, 25.1. (See appendix for details) Figure 2 )
[0064] Example 3: Preparation of M / CBT-10 composite electrode material (MXene:CBT=10:1)
[0065] (1) Take 100 mg of MXene powder prepared in Example 1, add 20 mL of deionized water, and ultrasonically disperse for 30 min to obtain a uniform MXene suspension;
[0066] (2) Weigh 10 mg of the CBT powder synthesized in Example 2, dissolve it in 10 mL of deionized water, and stir magnetically for 20 min until completely dissolved;
[0067] (3) Add 3 mg of ascorbic acid to the MXene suspension, and add CBT aqueous solution dropwise while stirring continuously for 1 hour;
[0068] (4) The mixture was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, sealed, and then kept at 180°C in an oven for 16 hours.
[0069] (5) Allow to cool naturally to room temperature, centrifuge to collect the solid, and wash three times with deionized water to remove free CBT and ascorbic acid;
[0070] (6) Dry in a vacuum oven at 60℃ for 24 hours to obtain black M / CBT-10 composite powder. ("M" refers to Ti3C2T) x MXene).
[0071] Example 4: Preparation of M / CBT-5 composite electrode material (MXene:CBT=5:1)
[0072] The preparation process is the same as in Example 3, except that the amount of CBT added is changed to 20mg, while the amount of other raw materials, hydrothermal temperature, heat preservation time and post-treatment conditions remain unchanged.
[0073] Example 5: Preparation of M / CBT-20 composite electrode material (MXene:CBT=20:1)
[0074] The preparation process is the same as in Example 3, except that the amount of CBT added is changed to 5mg, while the amount of other raw materials, hydrothermal temperature, heat preservation time and post-treatment conditions remain unchanged.
[0075] Example 6: Preparation of M / CBT-10 electrode sheet
[0076] (1) Powder ratio: 80wt% M / CBT-10 composite powder, 10wt% conductive carbon black, and 10wt% PVDF binder;
[0077] (2) Add an appropriate amount of N-methylpyrrolidone solvent, and planetarily stir and grind for 4 hours to obtain a uniform and viscous electrode slurry;
[0078] (3) The slurry is uniformly coated onto the titanium foil current collector by a scraper, and the wet film thickness is controlled at 100 μm;
[0079] (4) Dry in an oven at 80℃ for 12 hours to remove solvent, roll-press to compact, cut into 12mm diameter circular electrode sheets, and vacuum dry for later use.
[0080] Example 7: Assembly and Application of CR2032 Symmetrical Supercapacitor
[0081] (1) Electrolyte preparation: 1 mol / L H2SO4 aqueous solution; glass fiber diaphragm is selected;
[0082] (2) Take two M / CBT-10 electrodes prepared in Example 3 as positive and negative electrodes respectively, with a glass fiber diaphragm sandwiched in between;
[0083] (3) Add sufficient 1 mol / L H2SO4 electrolyte, pack it into the CR2032 battery casing, and seal it with a sealing machine; for electrochemical energy storage. See appendix for details. Figure 3 .
[0084] (4) Let it stand at room temperature for 12 hours to fully wet and activate it with electrolyte, and complete the preparation of symmetrical supercapacitor for electrochemical energy storage test.
[0085] Performance test results
[0086] (1) Three-electrode system (1M H2SO4, Ag / AgCl reference electrode, Pt counter electrode): 1 A / g -1 At current density, the specific capacitance of M / CBT-10 is 129.9 F / g. -1 It is superior to M / CBT-5 (108.1 F / g). -1 M / CBT-20 (101.5 F / g) -1 ), pure MXene (68.6 F / g) -1 ), pure CBT (40.6 F / g) -1 );
[0087] (2) Electrochemical performance of symmetric devices: stable voltage window 1.5V, 1 A / g -1 The specific capacitance of the device is 76.0 F / g. -1 Power density 750 W / kg -1 Energy density: 23.75 Wh / kg -1 After 5000 charge-discharge cycles, the capacity retention rate is 99.75% and the coulombic efficiency is 96.30%.
[0088] It should be further noted that the above embodiments are merely for understanding the technical solution of the present invention and are not intended to limit the scope of protection of the present invention. Any obvious adjustments and modifications made to the technical solution of the present invention that fall within the inventive concept should also fall within the scope of protection of the present invention.
Claims
1. A sulfur- and nitrogen-rich heterocyclic aromatic organic molecule composite electrode material, characterized in that, The composite electrode material contains Ti3C2T x MXene and sulfur- and nitrogen-rich heterocyclic aromatic organic molecules CBT; The molecular skeleton of the CBT contains both fluoren[2,3-b:3',2'-d]dithiophene and benzothiazole units, and the molecule is rich in S and N dual heteroatoms, possessing multi-electron reversible redox sites; the CBT molecule is embedded in the MXene interlayer, and the molecular conjugated π system generates π-π interaction with MXene, and the S and N heteroatoms of CBT form an electronic coupling interface with the Ti sites on the MXene surface.
2. The composite electrode material according to claim 1, characterized in that, The CBT has the following NMR characterization data: 1 HNMR(400 MHz, CDCl3): 8.04 (d, J = 3.6 Hz, 2H), 7.90 (d, J = 8.8 Hz, 2H), 7.83 (d, J = 6.8 Hz, 2H), 7.64\7.60 (m, 2H), 7.26\7.23 (m, 2H), 1.55 (s, 6H); 13 CNMR (101 MHz, CDCl3): 161.4, 155.6, 152.1, 139.8, 137.9, 137.4, 134.9, 129.7, 128.6, 127.3, 124.7, 123.5, 119.9, 118.0, 45.7, 25.
1.
3. A method for preparing the sulfur-rich nitrogen-rich heteroaromatic ring organic molecule composite electrode material as described in claim 1 or 2, characterized in that, Includes the following steps: (1) Ti3C2T x MXene powder was dispersed in deionized water to prepare an MXene suspension; (2) Dissolve CBT in deionized water to prepare an aqueous solution of CBT; (3) Add ascorbic acid to the MXene suspension, and add the CBT aqueous solution dropwise under stirring. Mix well to obtain a precursor mixture. (4) The precursor mixture is transferred to a hydrothermal reactor for hydrothermal intercalation reaction; (5) After the reaction is complete, the composite electrode material is separated, washed and dried to obtain the composite electrode material.
4. The preparation method according to claim 3, characterized in that, The Ti3C2T x The mass ratio of MXene to CBT is (5~20):
1.
5. The preparation method according to claim 3, characterized in that, The Ti3C2T x The mass ratio of MXene to CBT is 10:
1.
6. The preparation method according to claim 3, characterized in that, The hydrothermal intercalation reaction temperature is 180℃, and the reaction time is 16h.
7. The preparation method according to claim 3, characterized in that, The Ti3C2T x MXene powder was prepared by MILD etching, with the etchant being a mixed solution of LiF and hydrochloric acid, the etching temperature being 40℃, and the etching time being 48h.
8. The application of the composite electrode material according to any one of claims 1-2 or the composite electrode material prepared by the preparation method according to any one of claims 3-7 in supercapacitors.
9. A symmetrical supercapacitor, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The positive and negative electrodes respectively comprise the composite electrode material according to any one of claims 1-2, the electrolyte is an aqueous sulfuric acid solution, and the operating voltage window of the symmetrical supercapacitor is 0~1.5V.